Effect of larger corneal spherical aberration in improving the near visual acuity of eyes implanted with the TECNIS Symfony - Wang, Dandan; Liu, Chunlu; Guan, Weichen; Lu, Ziyi; Zhao, Yinying; Zhao, Yune (Frontiers in Medicine, 2023)
Purpose To explore the effect of corneal spherical aberration on the visual acuity and visual quality of eyes implanted with the TECNIS Symfony intraocular lens (IOL). Methods A total of 43 patients with age-related cataract (60 eyes) undergoing phacoemulsification and TECNIS Symfony IOL implantation were enrolled in this study. The uncorrected distance (UDVA), intermediate (UIVA), near visual acuity (UNVA), corrected distance visual acuity (CDVA), contrast sensitivity, and ocular spherical aberration were recorded 3 months after surgery. Preoperative and postoperative corneal spherical aberration were also measured using the iTrace device. Objective scattering index (OSI), modulation transfer function cut-off frequency (MTF cut-off), and Strehl ratio (SR) were measured by the Optical Quality Analyzing System. Catquest-9SF questionnaire were applied too. Spearman’s correlation analysis was used to evaluate the relationship between spherical aberration and visual quality parameters. Results Patients were satisfied with their postoperatively visual quality. And the postoperative logMAR UDVA, UIVA, UNVA, and CDVA was 0.05 ± 0.07, 0.04 ± 0.06, 0.15 ± 0.07, and 0.03 ± 0.05, respectively. The mean preoperative corneal spherical aberration was 0.24 ± 0.10 μm, which is the only factor influencing postoperatively UNVA, and it was negatively correlated with UNVA and glare contrast sensitivity under 18 cpd (cycle/degree, cpd) spatial frequency (r = −0.403, −0.300, −0.360; all P < 0.05). Additionally, the greater the residual spherical aberration of the cornea, the better the near vision after operation. The mean postoperative ocular spherical aberration was −0.03 ± 0.07 μm, it was not correlated with visual acuity, contrast sensitivity, and visual quality (all P > 0.05). Conclusion Preoperative positive spherical aberration can benefit near vision while decrease contrast sensitivities at high spatial frequencies when implanted with the TECNIS Symfony IOL.